PENGARUH KUALITAS PELAYANAN DAN NILAI PELANGGAN TERHADAP KEPUASAN ANGGOTA (Studi pada Koperasi Simpan Pinjam Langgeng Makmur Surabaya) - Ali Muhajir (eBA Journal: Journal Economic, Bussines dan Accounting, 2015)
This research take a title the Influences of service quality and Consumer Value TowardMember Satisfaction of Langgeng Makmur Cooperation which moved in lend and borrowfinancial service. This research purpose to recognize how variable role of service quality andconsumer value in order to increase member satisfaction of Langgeng Makmur CooperationSurabaya. From both independent variables that are service quality and consumer value whichone is dominantly role increasing satisfaction of cooperation member.Data collected through questionnaire method toward 74 respondents or service user ofLanggeng Makmur cooperation Surabaya that gained by using Simple Random Samplingtechnique. Analysis that used is multiple linear regression analysis with computer softwareaided SPPS 20.00.From the analysis yield can be concluded that service quality variable and consumervalue simultaneously have influence toward satisfaction level of member Langgeng Makmurcooperation Surabaya. It is compatible with hypothesis posed, get proved with calculationresult by using multiple linear regression method where gained value R2 as high 0,715 or71,50% member satisfaction influenced by service quality and consumer value variables whilethe rest is 28,5% influenced with other factor that uncalculated in this research. Then from bothindependent variables researched that are service quality and consumer value, based onvariable t-test or partial test can be concluded that most dominant which influence membersatisfaction level in Langgeng Makmur cooperation Surabaya is service quality variabel, whereit can be proved with regression value between service quality variable and membersatisfaction as many 0,642 or 64,20% member satisfaction influenced by service quality inassumption value consumer is nil and correlation value as 0,801 or 80,10% with significant level0,000 or far under alpha value as 0,05 or 5%.